2017
DOI: 10.1071/ch17062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gold Nanoparticles and Gold Anti-Arthritic Compounds on Inflammation Marker Expression in Macrophages

Abstract: The ability of aurothiomalate and auranofin to alter the production of several cellular mediators of inflammation by RAW264.7 macrophages, was compared with each other and that of gold nanoparticles (Au NPs). Addition of auranofin was found to have a pronounced ability to lower the production of reactive nitrogen and oxygen species (RNS and ROS respectively), as well as interleukin-10 (IL-10) and tumour necrosis factor (TNF), by macrophages that were subsequently treated with lipopolysaccharide (LPS) to stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
0
4
0
1
Order By: Relevance
“…Nevertheless, a study by James et al [ 212 ] reported contradictory results with mentioned studies. They revealed that gold compounds such as auranofin had a pronounced ability to decrease the production of several inflammatory mediators such as reactive NO, ROS, and TNFα by LPS-induced macrophages compared to GNPs.…”
Section: Application Of Gnps In the Management Of Autoimmune Disordersmentioning
confidence: 92%
“…Nevertheless, a study by James et al [ 212 ] reported contradictory results with mentioned studies. They revealed that gold compounds such as auranofin had a pronounced ability to decrease the production of several inflammatory mediators such as reactive NO, ROS, and TNFα by LPS-induced macrophages compared to GNPs.…”
Section: Application Of Gnps In the Management Of Autoimmune Disordersmentioning
confidence: 92%
“…In particular, TEM allows to reconstruct 3D images and determine the NPs cellular localization by sequential ultrathin specimen sections [ 120 ]. Field emission (FE) SEM can also be used to distinguish between intracellular and externally bound NPs with a resolution of 1 nm [ 121 ], by using different accelerator voltages [ 122 ]. In addition, electron microscopic techniques can be coupled with energy dispersive X-ray (EDX) analysis, and backscattered electron imaging (FE-SEM) to offer an ideal analytical platform for the characterization of NPs in and on the cells [ 123 , 124 ].…”
Section: Methods For Qualitative and Quantitative Analysis Of Cellmentioning
confidence: 99%
“…This method has an advantage of reducing the sample preparation steps and thus, preparation time while allowing resolution up to 1 nm. 125 Surface bound and intracellular NPs can be distinguished by using different accelerator voltages as demonstrated by James et al 126 Thus, coupled with energy dispersive X-ray analysis, and backscattered electron imaging FE-SEM offers an ideal analytical platform for the characterization of NPs in and on the cells. 127,128 Finally, the pioneering work of Havrdova et al 129 demonstrated that FE-SEM can be used to determine the cellular ultrastructural localization of NPs (Figure 8).…”
Section: Microscopy Methodsmentioning
confidence: 99%